Promoting the social integration of the eldery: housing rehabilitation and assistive technologies - Eloy, Sara (2012)
This paper addresses the need to respond to the new demographic reality, namely the increase of the elderly population, regarding new housing requirements. The research carried out focuses on defining housing rehabilitation strategies to fulfil the elderly needs and on how the integration of Information and Communication Technologies and Assistive Technologies (ICAT) in the dwelling space will assist this group of population and enable “ageing in place”.